Prediction of Aerodynamic Characteristics for Commercial Aircraft based on Open-Source Cruise Flight Data - Indriyanto, Toto; Hafizhuddin, Hafizhuddin (WARTA ARDHIA, 2024)
Airplane characteristics are interesting to analyze. The characteristics are shown as aerodynamic, structural and propulsion performance which further shows how economical the aircraft is compared to other aircraft. With the development of automatic dependent surveillance - broadcast (ADS-B), open source commercial aircraft flight data can be obtained easily. This study is performed to develop algorithm that can be used to predict aircraft aerodynamic coefficients. The algorithm is a collection of equations developed and simplified in previous studies. It is then used to estimate mass, lift, drag, and thrust forces, lift and drag coefficients, as well as fuel flow of an aircraft throughout the flight based on open source flight data, such as Flightradar24. The resulting lift and drag coefficients from the application of this algorithm are reasonably close within 9 – 14% compared to available references. Flightradar24 data is actually quite accurate for further flight performance analysis.